Head impact biomechanics in women`s college soccer - Lynall, R. C.; Clark, M. D.; Grand, E. E.; Stucker, J. C.; Litleton, A. C.; Aguilar, A. J.; Petschauer, M. A.; Teel, E. F.; Mihalik, J. P. (Medicine & Science in Sports & Exercise, 2015)
There are limited nonlaboratory soccer head impact biomechanics data. This is surprising given soccer`s global popularity. Epidemiological data suggest that female college soccer players are at a greater concussion injury risk than their male counterparts. Therefore, the purposes of our study were to quantify head impact frequency and magnitude during women`s soccer practices and games in the National Collegiate Athletic Association and to characterize these data across event type, playing position, year on the team, and segment of game (first and second halves).